THE INFLUENCE OF GREEN MARKETING, PRODUCT QUALITY AND CONSUMER CONFIDENCE ON PURCHASING DECISIONS FOR AVOSKIN SKINCARE PRODUCTS FOR STUDENTS OF THE FACULTY OF ECONOMICS AND BUSINESS, MALIKUSSALEH UNIVERSITY - Adnan; Rusydi Abubakar; Ikramuddin; Titi Yulmaida (RADJA PUBLIKA, 2024)
This study aims to analyze the effect of green marketing, product quality, and consumer confidence on purchasing decisions for Avoskin skincare products among students of the Faculty of Economics and Business, Malikussaleh University. The method used is quantitative with a survey approach. Data was collected through questionnaires distributed to 100 respondents selected by purposive sampling technique. Data analysis was carried out using multiple linear regression and also hypothesis testing. The results showed that green marketing, product quality, and consumer confidence have a significant and positive influence on purchasing decisions. Green marketing influences purchasing decisions by showing the company's commitment to the environment, while product quality influences through perceptions of product excellence and effectiveness. Consumer trust is a key factor that strengthens the relationship between product perceptions and purchasing decisions. These findings indicate that marketing strategies that focus on environmental aspects and product quality, as well as building consumer trust, can increase purchasing decisions for Avoskin skincare products among college students. This research is expected to contribute to the development of more effective marketing strategies in the skincare industry.